2018
DOI: 10.1111/jeu.12694
|View full text |Cite
|
Sign up to set email alerts
|

A Non‐Flagellated Member of the Myxogastria and Expansion of the Echinosteliida

Abstract: Myxogastria (also called Myxomycetes or plasmodial slime-moulds) are mostly known through their usually conspicuous fruiting bodies. Another unifying trait is the presence of a facultative flagellate stage along with the obligate amoeboid stage. Here we show with two-gene phylogenies (SSU rRNA and EF-1alpha genes) that the incertae sedis, non-flagellate Echinosteliopsis oligospora belongs to the dark-spore clade (Fuscisporidia) of the Myxogastria. In addition, we confirm that Echinostelium bisporum, firstly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…However, a well-developed capillitium with anastomosing branches separates Clastoderma from the Echinosteliales, which is supported by our 18S rDNA phylogeny (Fig. 2) and by the two-gene phylogeny of Fiore-Donno et al (2018). The homogenous upper portion of the stalk, connected to the capillitium in C. debaryanum, may represent an initial epihypothallic stalk, while the lower part seems to form via the intermediate way as in Echinosteliales.…”
Section: Classification Of the Myxomycetessupporting
confidence: 73%
See 1 more Smart Citation
“…However, a well-developed capillitium with anastomosing branches separates Clastoderma from the Echinosteliales, which is supported by our 18S rDNA phylogeny (Fig. 2) and by the two-gene phylogeny of Fiore-Donno et al (2018). The homogenous upper portion of the stalk, connected to the capillitium in C. debaryanum, may represent an initial epihypothallic stalk, while the lower part seems to form via the intermediate way as in Echinosteliales.…”
Section: Classification Of the Myxomycetessupporting
confidence: 73%
“…2), Clastoderma branches together with members of the superorder Stemonitidia but not with Echinosteliidia, with similar support of the corresponding clade. Independently, Fiore-Donno et al (2018) found the same topology in a phylogeny based on 18S rRNA and EF1A genes. We cannot ignore this result and thus separate Clastoderma from the Echinosteliales, although the hypothesis on the monophyly of both taxa could not be rejected by the Approximately Unbiased test and additional studies are needed with broader sampling of Clastoderma and Echinostelium to clarify the relationships between these taxa.…”
Section: ••• Subclass Columellomycetidaementioning
confidence: 63%
“…Myxomycetes constitute a terminal branch in the phylum Amoebozoa (Cavalier‐Smith ) and the main group in Macromycetozoa, along Dictyostelia and Protosporangiida ( Ceratiomyxa ) (Fiore‐Donno et al. ; Kang et al. ).…”
Section: Specimens Used In This Study Herbarium Number Location Comentioning
confidence: 99%
“…The main division in Myxomycetes lies between the superorders Lucisporidia and Fuscisporidia, characterized by bright and dark spore color, respectively (Fiore‐Donno et al. 2010b, ; Kretzschmar et al. ).…”
Section: Specimens Used In This Study Herbarium Number Location Comentioning
confidence: 99%
“…The close similarities in the life cycles of the protosporangids and myxomycetes point to homologous developmental programs. Indeed, Clark & Haskins (2014) hypothesized that the ancestral myxomycete formed fruiting bodies through a simple sporocarpy-like process, as found in the early-branching (Fiore-Donno et al, 2010, 2013Fiore-Donno, Tice & Brown, 2018) genera Echinostelium and Cribraria.…”
Section: The Multicellular Sporocarpy Hypothesismentioning
confidence: 99%